CHARACTERISTICS OF ON LANGUAGE TEACHING METHODS IN SCHOOLS (American Journal of Pedagogical and Educational Research, 2024)
This article analyzes the characteristics of native language teaching methods in schools of Uzbekistan. The research shows the importance of developing students’ practical language skills through modern approaches, effectiveness of communicative and interactive methods, project teaching and role-playing games in mother tongue classes. Also, the article presents the problems encountered in the process of teaching the mother tongue and recommendations for their solution. Based on the results of the research, it was emphasized the need to organize training courses for teachers, wide use of innovative methods and updating of educational materials.